Quantification and categorisation of microplastics in wild and aquaculture fish and in the water of the Aegean Sea - Botelho, Ana Lourenço (2021)
Plastic waste is recognised as a global threat to ecosystems. Microplastics may enter the food chain directly or indirectly in contaminated water or prey, respectively. Totally, 47 fishes from the inside and outside of aquaculture cages were analysed from Leros, a Greek island situated on the Aegean Sea. In addition, 11 samples of seawater were collected around aquaculture cages. The microplastics quantified were identified through a stereomicroscope and confirmed by a hot needle test. The results showed that in seawater and fish samples, fibres were the predominant type of microplastics, the main size was between 0.5 to 2 mm. Blue was the principal colour in fish and black was the principal colour in seawater samples. Furthermore, aquaculture and wild fishes are exposed to direct intake of microplastics from the seawater. This project demonstrates that the contamination and bioaccumulation of microplastics represent a real danger along the food chain.